Treatment of non-vital primary molar using lesion sterilization and tissue repair (LSTR 3Mix-MP) - Tania Saskianti; Udijanto Tedjosasongko; Irmawati Irmawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Root canal preparation and anatomic variations of deciduous teeth often cause the child patient uncooperative and sometimes the treatment failure. the non-threatening treatment and non-invasive approaches is needed to obtain a good cooperation from child patient. Purpose: The study was aimed to clinically evaluate the use of 3Mix-MP- a combination of antibacterial drugs, i.e. metronidazole, minocycline and ciprofloxacin (3Mix), and macrogol and propylene glycol (MP) - as pulp medicament on a necroses primary molar. Methods: Subject were the children patients of Pediatric Dental Clinic Universitas Airlangga Dental Hospital. Eight primary molars with pulp necroses due to dental caries were selected as samples. The treatment was done based on the concept of lesion sterilization and tissue repair (LSTR) therapy. A slice of 3 Mix-MP pastes was placed in the cavity and then sealed with glassionomer cement. Subjects were asked for recall visit in 1, 3 and 6 months post treatment, for clinical and radiographic evaluation. The antibacterial effect of 3 Mix-MP was compared with tempophore on mixed bacteria of pulp cavity which was isolated prior to therapy. The antibacterial effect was determined by measuring the inhibition zone after 24 hours anaerobe incubation. Results: Seven out of 8 subjects on recall visit showed no acute or chronic clinical symptoms, such as fistulae, abscess, purulent exudates, swelling or feel any pain during mastication. Microbiological test result showed LSTR 3Mix-MP had antibacterial effect higher than tempophore (p<0.001). Conclusion: The study revealed that 3Mix-MP treatment showed clinical and radiographic positive response on necrose primary molar.Latar belakang: Preparasi saluran akar dan variasi anatomi gigi sulung seringkali menyebabkan pasien anak tidak kooperatif dan kadang menyebabkan kegagalan perawatan. Perawatan yang tidak menakutkan dan non-invasif diperlukan untuk mendapatkan kerjasama yang baik dari pasien anak. Tujuan: Penelitian ini bertujuan untuk evaluasi klinis penggunaan 3Mix - MP- kombinasi obat antibakteri, yaitu metronidazole, minocycline dan ciprofloxacin (3Mix), dan makrogol dan propilen glikol (MP) – sebagai pengobatan pulpa pada gigi molar sulung yang nekrose. Metode: Subjek adalah pasien anak dari Klinik Kedokteran Gigi Anak Rumah Sakit Gigi & Mulut Universitas Airlangga. Delapan gigi molar sulung dengan nekrosis pulpa akibat karies gigi dipilih sebagai sampel. Pengobatan dilakukan berdasarkan konsep lesion sterilization and tissue repair (LSTR). Selapis pasta 3 Mix - MP ditempatkan di kavitas gigi dan kemudian ditumpat dengan semen glass-ionomer. Subjek diminta untuk kontrol untuk evaluasi klinis dan radiografi 1, 3 dan 6 bulan pasca perawatan. Efek antibakteri 3 Mix - MP terhadap bakteri campuran rongga pulpa yang diisolasi sebelum terapi dibandingkan dengan tempophore . Efek antibakteri ditentukan dengan mengukur zona hambat setelah 24 jam inkubasi anaerob. Hasil: Tujuh dari 8 subjek pada saat kontrol tidak menunjukkan gejala klinis akut atau kronis, seperti fistula, abses, eksudat purulen, bengkak atau merasa sakit selama pengunyahan. Hasil uji mikrobiologi menunjukkan LSTR 3Mix - MP memiliki efek antibakteri yang lebih tinggi daripada tempophore (p<0,001). Simpulan: Hasil penelitian menunjukkan bahwa penggunaan 3Mix - MP memberikan respon positif pada perawatan molar sulung yang nekrotik secara klinis dan radiografis.